Kampung Cukur Bojonggede As A Storytelling-Based Tourism Village Model - Ayat Taufik Arevin (LPPM and Travel Operation Department Universitas Asa Indonesia, 2021)
Bojonggede is prepared to become a tourist village with the icon of Kampung Cukur. This proposal is based on the phenomenon of many people working as barbers. Barber became the main actor in the dissemination of tourist attraction information. They need to be empowered when it comes to storytelling competence. Guiding technique training are delivered by AKPINDO lecturers and students through mentoring programs in community service projects. The mentoring program begins with activities to record the potential of tourism in Bojonggede village. The data was collected through field survey methods, FGD, interviews of community leaders, and hearings to the village, sub-district, and Bogor district heads. The study of Betawi cultural literature is used to reinforce the results of the description. The results of the study were able to inventory that Bojonggede can be developed as a tourism village based on culture, history, authentic natural environment, and community achievements in micro-entrepreneurs who can enrich tourism potential. Furthermore, counseling techniques guide the concept of Storytelling. So that the skills of the community, especially barbers can be developed. Storytelling training can build the trust and professionalism of the local community as a tourism business.